Community Rehabilitation for Families of persons Convicted of Terrorism, Field study in Anbar provincem - Maysam Yaseen Obaid,; Maha Karim Ali, (Technium Social Sciences Journal, 2020)
Iraqi society, like other societies, witnessed social, economic and political changes after 2003. These changes have increased social problems within the community. Terrorism is one of the main phenomena that spread at that time. Many terrorist organizations have emerged in Iraqi society, whose social fabric, political stability and economic activity are at risk. The most dangerous of these organizations appeared in 2014, when they controlled a third of the governorates of Iraq. They have destroyed many cities and practiced brutal and inhumane methods against members of Iraqi society, such as rape, detention, displacement, and the recruitment of children, youth and families. These methods have led to many problems, including the problem of families of those convicted of terrorism and their effects on the individual or society. Therefore, this research aims to give special importance to the rehabilitation of these families and their integration into society. It aims to define social rehabilitation programs for families of those convicted of terrorism and to understand the nature of these programs. It seeks to determine the reasons for joining terrorist organizations. It also highlights the social reality of families of those convicted of terrorism, in Anbar Governorate and Habbaniyah city in particular, In order to improve the living conditions of these families and achieve opportunities for social integration so that they can achieve social integration within the community. The study relied on the descriptive and analytical method and the method of a social survey by taking a sample of (250) families.